2017
DOI: 10.3390/e19110614
|View full text |Cite
|
Sign up to set email alerts
|

How to Identify the Most Powerful Node in Complex Networks? A Novel Entropy Centrality Approach

Abstract: Centrality is one of the most studied concepts in network analysis. Despite an abundance of methods for measuring centrality in social networks has been proposed, each approach exclusively characterizes limited parts of what it implies for an actor to be "vital" to the network. In this paper, a novel mechanism is proposed to quantitatively measure centrality using the re-defined entropy centrality model, which is based on decompositions of a graph into subgraphs and analysis on the entropy of neighbor nodes. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 66 publications
1
39
0
Order By: Relevance
“…For the binary karate club network, all vertex centralities identify either vertex 1 or vertex 34 as most important. These findings confirm previous studies [62][63][64][65] .…”
Section: A Zachary's Karate Club Networksupporting
confidence: 93%
“…For the binary karate club network, all vertex centralities identify either vertex 1 or vertex 34 as most important. These findings confirm previous studies [62][63][64][65] .…”
Section: A Zachary's Karate Club Networksupporting
confidence: 93%
“…Measuring II of a host is essential to capturing the intricacies of pathogen sharing not covered by the conventional measures analysed above, namely the range and speed by which host species propagate their pathogens to their neighbours. In this, our measure is similar to other entropy-based measures [34], as well as to established influence measures such as Katz centrality [28, 29], but it focuses on the species influence in its neighbour space rather than across the whole network. To further assess the relationship between II and established centrality metrics, we performed a correlation analysis of centrality measures in our networks which revealed that II correlated (on average across all networks) with closeness [29] (0.88) and Opsahl closeness [24] (0.82) centralities, and showed least correlation with OBC (0.16).…”
Section: (C) Novel Metric Of Node Influence: Indirect Influencementioning
confidence: 99%
“…In [ 48 , 49 , 50 , 51 , 52 , 53 , 54 ], the authors have demonstrated that better results of quantitative analyses of influence can be obtained by using entropy theory. In our previous work [ 55 ], the same conclusion has been drawn that defined entropy centrality has proven far superior to other widely used methods, such as degree centrality, betweenness centrality, closeness centrality, Eigenvector centrality, and PageRank. It is clear that the ideal algorithm, free of any limitations or assumptions, does not exist.…”
Section: Introductionmentioning
confidence: 74%